Influence of screen printing parameters on the front metallic electrodes geometry of solar cells. (2014) - ,; ,
Abstract : Purpose – The paper aims to present results of investigations carried out on the front electrode of the solar cell. The front‐side electrode for solar cells based on crystalline material is obtained by the screen printing method. Screen printing has been the prevailing method of electrode deposition because of its low cost. One of the ways to improve the cell efficiency and reduce the production costs is a further refinement of the metal electrode screen printing process.Design/methodology/approach – The researches were focused on the modification of mechanical parameters of screen printing process to ensure the best possible cross‐section of the front electrode geometry. The main printing process parameters were constant, however, the print speed was variable. The obtained fine line of front contact was characterized morphologically – the dimension and geometry of the front contact cross‐section – by scanning electron microscopy technique.Findings – The thin paths of 100 μ m in width were screen printed applying a new silver‐paste made by Du Pont. The printing speed has significant effect on print quality in the way that the lower speed enhanced the printed results.Research limitations/implications – For newest pastes (e.g. PV17D) influence of screen printing parameters on the front metallic electrodes geometry of solar cell is not so significant. Presented screen printing process can still give good results, but the further optimization for the new paste must be performed to achieve better cross‐section geometry.Originality/value – This paper confirms that one‐step screen printing process can still give good results. The screen printed thin paths of 100 μ m in width have good cross‐section aspect ratio. Acknowledgements : This work was supported under statutory works of IMMS of PAS.